Breakthrough : how one teen innovator is changing the world - Andraka, Jack (Speaking Tiger, 2015)
"Teen scientist Jack Andraka chronicles his development of an inexpensive early detection test for pancreatic, ovarian, and lung cancer, and recounts his own personal story of overcoming depression and homophobic bullying. Includes hands-on science experiments"--From publisher description.